Identification and Characterization of Perennial Ryegrass (Lolium perenne) Vernalization Genes - Herridge, Rowan; Samarth,; Brownfield, Lynette; Macknight, Richard (Frontiers in Plant Science, 2021)
Perennial ryegrass (Lolium perenne) is a temperate grass species commonly used as pasture for livestock. Flowering (heading) of ryegrass impacts metabolizable energy content and seed yield, therefore this trait is important for both farmers and seed producers. In related grass species, the VRN genes (VRN1-3) have been largely implicated in the determination of vernalization response and are responsible for much of the intra-species variation in this trait. Many other important flowering-time regulators have been catalogued in the model grass Brachypodium distachyon; however, in several cases, such as VRN2, their ryegrass homologs have not been well-characterized. Here, ryegrass homologs of important flowering time genes from B. distachyon were identified through available synteny data and sequence similarity. Phylogenetic analysis of VRN3/FT-like and VRN2-like genes was performed to elucidate these families further. The expression patterns of these genes were assessed during vernalization. This confirmed the key roles played by LpVRN1 and LpFT3 in the promotion of flowering. Furthermore, two orthologs of VRN2 identified here, as well as an ortholog of CO9, were expressed prior to vernalization, and were repressed in flowering plants, suggesting a role in floral repression. Significant variability in expression of these flowering pathway genes in diverse genotypes was detected and may underlie variation in flowering time and vernalization response.